A Novel Pak1/ATF2/miR-132 Signaling Axis Is Involved in the Hematogenous Metastasis of Gastric Cancer Cells - Funan Liu; Zhenguo Cheng; Xiaodong Li; Yanshu Li; Hongyan Zhang; Jiabin Li; Furong Liu; Huimian Xu; Feng Li (Elsevier, 2017)
We, along with others, have shown previously that P21-activated kinase 1 (Pak1) plays a pivotal role in gastric cancer progression and metastasis. However, whether Pak1 controls gastric cancer metastasis by regulating microRNAs (miRNAs) has never been explored. Here, we report a novel mechanism of Pak1 in tumor metastasis. A detailed examination revealed that Pak1 interacts with and phosphorylates the serine 62 residue of ATF2 and then blocks its translocation into the nucleus. We also confirmed that ATF2 binds to the promoter of miR-132 and tightly regulates its transcription, thus explaining the regulatory mechanism of miR-132 by Pak1. miR-132 also significantly reduced cell adhesion, migration, and invasion of gastric cancer cells in vitro and significantly prevented tumor metastasis in vivo. miR-132 specifically inhibited hematogenous metastasis, but not lymph node or implantation metastases. In order to further delineate the effects of the Pak1/ATF2/miR-132 cascade on gastric cancer progression, we identified several targets of miR-132 using a bioinformatics TargetScan algorithm. Notably, miR-132 reduced the expression of CD44 and fibronectin1 (FN1), and such inhibition enabled lymphocytes to home in on gastric cancer cells and induce tumor apoptosis. Taken together, our studies establish a novel cell-signaling pathway and open new possibilities for therapeutic intervention of gastric cancer. Keywords: p21-activated kinase 1, activating transcription factor-2, miR-132, hematogenous metastasis